A Comprehensive Literature Review of Consumption of 100% Fruit Juice and Body Weight in Children and Adults - Steven, Steven; Adrian, Adrian; Widia, Widia (International Medical Journal Corp. Ltd, 2024)
Background: The literature on the consumption of 100% fruit juice and its implications for body weight in children and adults reveals a nuanced and often contentious landscape. The introduction establishes the importance of distinguishing between 100% fruit juice and sugar-sweetened beverages, a point underscored by (Benton & A Young, 2019), who argue that conflating these two categories may lead to misleading conclusions regarding health outcomes. Their analysis indicates that while some studies suggest a long-term weight increase associated with fruit juice consumption, this may not apply to 100% fruit juice, which holds a different nutritional profile. Literature Review: Collectively, the literature indicates that while there are concerns about the caloric density and lower fiber content of 100% fruit juice, its role in enhancing diet quality and meeting nutritional needs cannot be overlooked. The evidence suggests that moderate consumption of 100% fruit juice may not be directly linked to increased body weight, particularly when compared to sugar-sweetened beverages. The ongoing debates underscore the need for continued research to disentangle the effects of 100% fruit juice from those of added sugars and to better understand its place within broader dietary patterns. Conclusion: In conclusion, the current body of literature presents a complex interplay between 100% fruit juice consumption, nutrient intake, and body weight. While some studies indicate potential risks associated with juice consumption, others highlight its contributions to diet quality and nutritional adequacy, especially in vulnerable populations. The findings collectively advocate for a more nuanced understanding of the role of 100% fruit juice in dietary habits and its implications for health outcomes.